2014
DOI: 10.1097/bpo.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

A Line Drawn Along the Radial Shaft Misses the Capitellum in 16% of Radiographs of Normal Elbows

Abstract: Diagnostic Level 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…When combined with careful clinical examination and a thorough understanding of the radiographic interpretation, especially in young children, the RCL still can assist in the evaluation of the elbow joint and ultimately may lead to better treatment and outcomes. In agreement with previous studies, 18,19 if subtle malalignment is suspected in the skeletally immature elbow, alternative imaging modalities such as ultrasonography, MRI, and/ or arthrography to better visualize the cartilaginous articular configuration and alignment should be considered.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…When combined with careful clinical examination and a thorough understanding of the radiographic interpretation, especially in young children, the RCL still can assist in the evaluation of the elbow joint and ultimately may lead to better treatment and outcomes. In agreement with previous studies, 18,19 if subtle malalignment is suspected in the skeletally immature elbow, alternative imaging modalities such as ultrasonography, MRI, and/ or arthrography to better visualize the cartilaginous articular configuration and alignment should be considered.…”
Section: Discussionsupporting
confidence: 60%
“…This lack of consistency concurs with previous publications, which reported that younger patient ages correlated with less RCL accuracy in both planes. 18,19 Moreover, when the RCL missed the central third of the ossified capitellum, it deviated exclusively to intersect the posterior third on the sagittal plane and the lateral third on the coronal plane (Fig. 3).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…examined the reliability of this landmark in normal pediatric elbows and found that in 8.6% of elbows the radiocapitellar line did not intersect the capitellum. 10 They found that this measurement was more accurate when the line was drawn through the radial head rather than the neck, and that it was less likely to miss the capitellum in patients older than 5 years. 10 …”
Section: Radiographic Relationshipsmentioning
confidence: 99%